Nasiba HORTICULTURE TERMS AS A SYSTEM OF WORLD SCIENTIFIC TERMINOLOGY: HORTICULTURE TERMS AS A SYSTEM OF WORLD SCIENTIFIC TERMINOLOGY - Suyundikova, Nasiba (Журнал иностранных языков и лингвистики, 2022)
Horticulture is an ancient pursuit. Beginning some 10,000 years ago, our brilliant forebears discovered the horticultural craft secrets that are the basis of our profession. They initiated a revolution that changed forever the destiny of humans from scavenging, collecting, and hunting to agriculture. We all are the heirs and beneficiaries of this legacy from the past. Our roots derive from prehistoric gatherers, Sumerian, Egyptian, Chinese, and Korean farmers, Hellenic root diggers, medieval peasants, and gardeners everywhere who devised practical solutions to problems of plant growing for food, ornament, medicine, fiber, and shelter. The accumulated successes and improvements passed orally from parent to child, from artisan to apprentice, and became embedded in human consciousness via legend, craft secrets, and folk wisdom. It was stored in tales, almanacs, herbals, and histories and has become part of our common culture. More than practices and skills were involved as improved germplasm was selected and preserved via seed and graft from harvest to harvest and generation to generation.